(untitled) (Baltic Journal of Sport and Health Sciences, 2016)
Background. Research literature highlights the need to use objective assessment tools to quantify muscle tone because all typically used clinical scales of muscle tone have reliability problems. Though hand-held device Myoton-3 has been used in research with children, its reliability has not been established. The aim of this study was to investigate intrarater and interrater reliability of muscle tone, elasticity and stiffness measurements by Myoton-3 in healthy children aged 5–7 years. Methods. A total of 30 healthy children aged between 5 and 7 years participated in the study. Myoton-3 device was used by two measurers to assess tibialis anterior (TA), rectus femoris (RF), biceps brachii (BB), medial head of gastrocnemius (GM), biceps femoris (BF), trapezius (TR) and triceps brachii (TB) muscle tone, elasticity and stiffness values. Measurements were conducted for intrarater reliability on two consecutive days and for interrater reliability on the same day. Results. Intrarater reliability expressed as intra-class correlation of frequency, decrement and stiffness characteristics measurements was moderate to high, between 0.60–0.72, while TR muscle ICC was low. Interrater reliability expressed as intra-class correlation of the frequency, decrement and stiffness characteristics measurements was high to very high, between 0.72–0.91, while TR muscle ICC was low. Conclusion. Moderate to high (0.60–0.72) intrarater reliability and high to very high interrater reliability (0.72– 0.91) was established for Myoton-3 measurements in healthy children aged 5–7 years. The Myoton-3 is a reliable device for measuring skeletal muscle tone, elasticity and stiffness in preschool children.